Teaching Mahfuzat as a Medium for Internalizing Islamic Values and Ethical Conduct - Rachman, Lutfi (Al-Munawwarah: Journal of Islamic Education, 2025)
In many Islamic educational settings, the teaching of Arabic often emphasizes rote linguistic mastery rather than the internalization of moral and spiritual values. Within pesantren contexts, mahfuzat concise Arabic maxims have long served as a traditional medium linking language learning with ethical and spiritual formation. The research aims to identify core values embedded in selected verses from Ustaz Qoimuddin’s Jawāhir al-Maḥfūẓāt and to analyze how those values are internalized through classroom practice. Using a qualitative descriptive design, data were collected from 30 first-year Tsanawiyah students at Pondok Pesantren Darullughah Wadda’wah via classroom observation, semi-structured interviews, and text analysis. Findings show five interrelated value themes—pursuit of knowledge, humility, righteous companionship, respect for teachers, and perseverance—becoming habituated through a three-phase cycle: memorization (ḥifẓ), understanding (tafahhum), and embodiment (tatbīq). Rhythmic recitation and dialogic reflection enable students to connect linguistic beauty with ethical intent, while the Arabic-using school environment strengthens value absorption in daily interactions. The impact of this approach is a demonstrable integration of linguistic proficiency, ethical awareness, and spiritual sensitivity. The study concludes that teaching mahfuzat offers a culturally authentic, scalable model of value-based language education that revitalizes the classical harmony of ‘ilm, adab, and taqwā in contemporary Islamic schooling.